PEMANFAATAN SAMBA SERVER DALAM PERTUKARAN DATA BERBASIS CLIENT SERVER - febri romadhon; toibah umi kalsum; eko prasetyo rohmawan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Junior High School 8 Lubuk Linggau is one of the schools located in Lubuk Linggau City in South Sumatra Province. It has already 30 computers in the Laboratory, but the computers are not connected to each other, so it is often difficult for the teachers who teach in sending files to all computers. The purpose of this research is to utilize Samba Server in Client Server-Based Data Exchange. The research method used is the Network Development Life Cycle (NDLC) method. The samba installation and configuration process is successful, and the client can access files that have been shared by the server. Network configuration for Laptop Server with IP Address 192.168.1.1, Laptop Clientwith IP Address 192.168.1.2 through 192.168.1.50. Base don the testing that has beendone, a computer that is used as a server often lags/error freezes, thus a server computer with more adequate specifications is needed. The suggestion from the researcher is tobe able to use a file sharing system using samba server, where the files that will be shared are on the file server.